Inovasi dan Keberlanjutan Bisnis UMKM di Era Digital: Kajian Literatur Sistematis - Sinta Istamarina; Erna Anggraeni; Dwi Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study explores the impact of digital transformation on Micro, Small and Medium Enterprises (MSMEs) in Indonesia, emphasizing the importance of innovation and sustainability in today's digital landscape. This research highlights the important role of digital technology, such as e-commerce platforms and digital payment systems, in improving the operational efficiency and market reach of MSMEs. Despite the potential benefits, the research reveals that only 12% of MSMEs have successfully integrated digital technology into their operations, indicating a major gap that needs to be addressed. The findings show that cultivating a culture of creativity and innovation in MSMEs is critical to improving their performance and ensuring long-term sustainability. Additionally, government initiatives aimed at improving the digital capabilities of MSMEs were discussed, showcasing the collaborative efforts needed to support the sector. Overall, this research underscores the need for continued support and resources to help MSMEs thrive in an increasingly digital economy.